Behaviour of Reinforced Concrete Deep Beams with Openings in the Shear Zone - Chin, Siew Choo; Doh, Shu Ing (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
Reinforced concrete (RC) deep beams are useful in high rise building to support high loading in a structure. In RC deep beam construction, openings are usually provided in beam for accessibility purpose and to accommodate essential services such as power supply, ventilation system and network system access. However, the presence of openings in deep beams may lead to many problems in the beam behaviour such as reduction in the beam capacity, cause excessive cracking and deflection. Hence, this study was conducted in order to study the behaviour of RC deep beams openings. Two openings, one in each shear span, were placed symmetrically at the top of shear span near support about the mid-point of the beam. Test parameters included the opening size and shape. The openings were circular and square in shape. The sizes of the openings considered in this study include 150 mm, 200 mm and 250 mm for circular whereas the size of square shape includes 150x150 mm, 200x200 mm and 250x250 mm. All the beam specimens had a cross-section of 100 mm x 500 mm and a total length of 1200 mm. The beams were tested under four-point bending until failure. The results in terms of load deflection behaviour and crack patterns were discussed. From the results obtained, the provision of circular opening with the diameter considered could reduce the beam capacity to a range of 30 – 35% of the original beam capacity. Meanwhile, the inclusion of square openings with openings of the considered dimension causes a significant loss of beam strength, about 40 – 80% as compared to the beam capacity of the solid beam. This shows that the greater the opening size, the more significant is the reduction of beam capacity with more severe and excessive diagonal shear cracks. Comparing in terms of shape, circular opening is the most suitable option to be provided in RC beams as square openings consists of sharp corners which is subjected to high stress concentration that leads to initial cracking in beam.